Performance comparison of hybrid active power filter for p-q theory and SVPWM technique - Thamizh Thentral, T. M.; Vijayakumar, K.; Jegatheesan, R. (International Journal of Electrical and Computer Engineering (IJECE), 2021)
Harmonic Distortion in many of the industrial applications are occur primarily owing to the enormous utilization of loads with high non-linearity like power converters, speed varying drives and arc furnaces. The power semiconductor is used to achieve the variation in speed and conversion from one source to another. Mostly active filters and tuned filters are utilized to remove the harmonic included in the source current. The tuned passive filters and inductance inserted in the line reduces the harmonics but at the same time induces the resonances in most of the industrial applications. Due to this, harmonic distortion increases in the source current and voltage. This can be reduced by adding hybrid filter in the system with decreased rating of active filter in high power applications. This article deals with the various topology of hybrid filters. The working of the proposed filter design in variable inductance mode based on the pollution created in the source voltage and current is studied. In the proposed hybrid filter passive filter is tuned with seventh harmonic frequency and connected in series with active filters to reduce the harmonic distortion. DC link voltage and the active filter VA rating could be minimized. The control signal to the filter is derived from p-q theory and space vector pulse width modulation (SVPWM). The performance of the system under study is simulated and noted for the THD percentage before and after the filter is added to the system and the same model is experimented with reduced voltage level.